Carbon monoxide poisoning mitigation approaches for the anode of polymer electrolyte membrane fuel cells - Seyyed Mohsen Mousavi Ehteshami (2013)
Carbon monoxide (CO) poisoning mitigation is an important technological and fundamental challenge in the field of polymer electrolyte membrane fuel cells (PEMFC’s). The presence of CO even in very low concentrations (a few tens of ppm level) is the main source of overpotential loss in the anode of PEMFC’s. Therefore, the fundamental understanding of CO poisoning and providing mitigation approaches for this issue is of great interest. The possible approaches to solve the CO poisoning of PEM fuel cells can be categorized into two main technologies: on-fuel cell and off-fuel cell approaches. In this dissertation, a combination of electrochemical studies and numerical simulations are carried out to understand the mechanism of CO poisoning, and two different approaches are investigated to mitigate this issue: 1) Electrocatalysts with enhanced CO tolerance are studied; 2) An electrolytic selective CO removal system based on electrochemical water gas shift reaction is developed.